2014
DOI: 10.1007/s00424-014-1524-0
|View full text |Cite
|
Sign up to set email alerts
|

Na+,HCO3 −-cotransport is functionally upregulated during human breast carcinogenesis and required for the inverted pH gradient across the plasma membrane

Abstract: Metabolic and biochemical changes during breast carcinogenesis enhance cellular acid production. Extrusion of the acid load from the cancer cells raises intracellular pH, while it decreases extracellular pH creating an inverted pH gradient across the plasma membrane compared to normal cells and promoting cancer cell metabolism, proliferation, migration, and invasion. We investigated the effects of breast carcinogenesis on the mechanisms of cellular pH control using multicellular epithelial organoids freshly is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(91 citation statements)
references
References 39 publications
8
83
0
Order By: Relevance
“…Moreover, some isoforms of NBC might play a vital role on the development of oral carcinogenesis. Indeed, it has been found that the enhancement of NBC activity is the main reason for an alkaline shift (~0.3 units of magnitude) in steady-state intracellular pH of human primary breast carcinomas compared to normal breast tissue [54]. Furthermore, upregulated NBCn1 during human breast carcinogenesis contributes to the characteristic acid distribution within human breast carcinomas [54].…”
Section: Potential Role Of Inhibitors/activators Of Isoforms Of Nhe Amentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, some isoforms of NBC might play a vital role on the development of oral carcinogenesis. Indeed, it has been found that the enhancement of NBC activity is the main reason for an alkaline shift (~0.3 units of magnitude) in steady-state intracellular pH of human primary breast carcinomas compared to normal breast tissue [54]. Furthermore, upregulated NBCn1 during human breast carcinogenesis contributes to the characteristic acid distribution within human breast carcinomas [54].…”
Section: Potential Role Of Inhibitors/activators Of Isoforms Of Nhe Amentioning
confidence: 99%
“…Indeed, it has been found that the enhancement of NBC activity is the main reason for an alkaline shift (~0.3 units of magnitude) in steady-state intracellular pH of human primary breast carcinomas compared to normal breast tissue [54]. Furthermore, upregulated NBCn1 during human breast carcinogenesis contributes to the characteristic acid distribution within human breast carcinomas [54]. Therefore, our present study has provided a new strategy of potential role of inhibitors/ activators of isoforms of NHE and NBC in clinical setting.…”
Section: Potential Role Of Inhibitors/activators Of Isoforms Of Nhe Amentioning
confidence: 99%
“…Na + /H + exchanger Nhe1 contributes to regulatory cell volume increase, which is in part accomplished by parallel activity of Na + /H + and Cl - /HCO 3 - exchanger [55, 56]. Increase of cell volume is a precondition for cell proliferation and stimulation of cell proliferation is paralleled by a shift of Na + /H + exchanger cell volume regulatory set point to larger volumes [57-59].…”
Section: Discussionmentioning
confidence: 99%
“…NHE1 does not always play an exclusive, predominant role in the pHregulation of cancer cells. In human breast cancer carcinomas, for instance, the expression of NBCn1 is twofold higher compared to normal breast cancer tissue obtained from the same patient [118,121]. This is accompanied by an increase in the clearly NBCn1-mediated cellular net-acid extrusion (=HCO 3 -import) leading to an alkaline shift in the steady-state pH i by ~0.3 pH units.…”
Section: Accepted Manuscriptmentioning
confidence: 94%